A Case Study in West Nusa Tenggara for Automated Feedback of Performance Assessment on Science Practicum to Measure Science Process Skills in University - Sudirman Sudirman; Agus Ramdani; Aris Doyan; Yunita Arian Sani Anwar; Joni Rokhmat; AA. Sukarso (Postgraduate, University of Mataram, 2023)
This study examines respondent and university type responses to science process skills instruments integrated with automated feedback on science practicum performance assessments at 2 state college and 2 private college in West Nusa Tenggara Province. A Kruskal-Wallis test was performed utilizing case study and cluster random sampling. Data was collected using online survey, interviews, and direct observations. Three hundred seventy-six university students and teachers from four universities were studied. Since there was no standard instrument, science process skills performance was not assessed. The assessment results show no statistically significant difference (p > 0.05) between state and private college in measuring science process skills integrated with real-time feedback on science practicum. This suggests that neither university has conducted such an assessment. No significant difference in responses between university students and lecturers regarding the measurement of science process skills on performance assessments integrated with real-time feedback in science practicum (p > 0.05), implying that university students and lecturers have the same experience. This study advises developing science process skills measurement on performance assessment for real-time science practicum feedback.